Methotrexate-induced malabsorption in children with acute lymphoblastic leukaemia. Issue 6101 (10th December 1977) - Craft, A W; Kay, H; Lawson, D N; McElwain, T J
Abstract : A one-hour D-xylose absorption test was performed on 18 children with acute lymphoblastic leukaemia. Xylose absorption was normal in children who had not received methotrexate, but there was a significant degree of malabsorption in those who had taken methotrexate within the previous seven days. There was a progressive and significant increase in malabsorption related to the cumulative dose of methotrexate. These findings provide further evidence that regular methotrexate treatment every seven days is more toxic than if it is more widely spaced. The spacing of treatment is currently under investigation.